PENGARUH ANGGARAN PENDIDIKAN, TINGKAT KEMISKINANDAN KETIMPANGAN TERHADAP PRODUK DOMESTIK REGIONAL BRUTO DI PROVINSI ACEH - Affandi Affandi; T. Zulham; Eddy Gunawan (Jurnal Ekonomi dan Kebijakan Publik Indonesia, 2017)
This research aims to know the influence of the educational budget, poverty and inequality against GRDP Aceh province. The research method used is quantitative research. The data used is the data time series 2010-2015 and cross section 23 county/city in Aceh province. Secondary data is sourced from the Ministry of finance and the Central Bureau of statistics. Analytical techniques used is regression analysis with panel data model parameter estimation using the fixed effect model (FEM) weighted. The data used is the data panel during the Years 2010-2015.Research results show that the education budget and inequality of positive and significant effect against the GRDP, while the variable rates of poverty and significant negative effect against the GRDP. The value of the coefficient of determination (adj. R2 = 0,9966) shows that the free variables, educational budget, the poverty and inequality are able to explain variations from the variable, i.e., GRDP her factors not included in a model or explained in error term (e).